Islamic Education Management and Social Change And Development In Indonesia - Hadial Putra; Kasful Anwar; Asa'ad Isma (Cita konsultindo, 2023)
Management of Islamic education is a very important thing when looking at the existence of Islamic education itself. In order to continue to exist and develop, Islamic education clearly requires good management, which is planned and neatly arranged. So that it can develop the existence of Islamic education in the midst of global competition. Every human life is always experiencing changes. Social changes that occur in society can occur due to the process of human spread (diffusion) from one individual to another. This is because the process of social change does not only originate through an evaluation process, but can also occur through the process of spreading cultural elements between communities. Humans in their daily lives cannot be separated from culture, because humans are creators and users of culture itself. Humans live because of culture, meanwhile culture will continue to live and develop when humans want to preserve culture and not destroy it. Thus humans and culture cannot be separated from one another, because in life it is impossible not to deal with the results of culture, every day humans see and use culture, sometimes even realizing it or not humans destroy culture . Humans in their daily lives cannot be separated from culture, because humans are creators and users of culture itself. Humans live because of culture, meanwhile culture will continue to live and develop when humans want to preserve culture and not destroy it. Thus humans and culture cannot be separated from one another, because in life it is impossible not to deal with the results of culture, every day humans see and use culture, sometimes even realizing it or not humans destroy culture.